Strategic Asset-seeking Activities of Emerging Multinationals: Perspectives of Foreign Acquisitions by Indian Pharmaceutical MNEs - Pradhan, Jaya Prakash (Organizations and Markets in Emerging Economies, 2010)
While in general, studies on foreign acquisitions by emerging multinationals (EMNEs) have predicted these acquisitions to be driven by both market-seeking and strategic resource-seeking motivations, more concrete analyses on this topic are limited. This paper contributes to the existing literature by analyzing the overseas acquisition activities of EMNEs from Indian pharmaceutical sector. Using the general framework of technological change in emerging economies, Indian pharmaceutical firms are identified to have delicate weakness in their product development capabilities to face intensifying competition in the globalized policy regime. It makes sense for these firms to internationalize through acquisitions of foreign assets that help them not only access new markets but also new products and technologies to overcome their limited product development competencies. The empirical findings highlight the role of host market size, intensity of patenting, skill and liberal FDI policy regime as the key determinants of the geographical distributions of Indian pharmaceutical acquisitions. This implies that EMNEs from Indian pharmaceutical industry are using acquisition as a mixed strategy of accessing markets as well as strategic assets/resources.